Association of age at menopause and age at menarche with later-life skeletal fragility fractures in Bosnian postmenopausal women - Rubina Alimanović-Alagić; Martina Bonić; Dženan Pleho; Amila Kapetanović; Gordan Bajić; Sabina Sarić (Medicinski glasnik, 2023)
Aim: To investigate the effects of estrogen-related events (age at menopause, age at menarche) on later-life skeletal fragility in Bosnian postmenopausal women. Methods: A total of 100 postmenopausal Bosnian women, aged between 55 and 75 years, were included. The women in the study group (n=50) had fragility fractures, and in the control group (n=50) were without fragility fractures. Bone mineral density (BMD) was measured using Dual Energy X-ray Absorptiometry (DXA) on the lumbar spine (L2-L4) and proximal femur. Results: No statistically significant difference relating to the age between the groups was found. The average age at menopause was 44.70 years in women with fragility fractures and 51.76 years in women without fragility fracture (p=0.0001). The average age at menarche was 14.30 years in women with fragility fractures and 13.70 years in women without fragility fractures (p=0.140). T score of ?-2.5 SD was found in 40 (80%) women in the study group, and in eight (16%) women in the control group (p=0.0001). Conclusions: Age at menopause, but not age at menarche, was risk factors for later-life fragility fracture in postmenopausal Bosnian women. In addition, fragility fractures correlated with low BMD in this population group.
Keywords: fragility fracture; menarche; menopause